A pathogenic variant in the uncharacterized RNF212B gene results in severe aneuploidy male infertility and repeated IVF failure. - Gershoni, M.; Braun, T.; Hauser, R.; Barda, S.; Lehavi, O.; Malcov, M.; Frumkin, T.; Kalma, Y.; Pietrokovski, S.; Arama, E.; Kleiman, S.E. (HGG advances, 2023)
Quantitative and qualitative spermatogenic impairments are major causes of men's infertility. Although in vitro fertilization (IVF) is effective, some couples persistently fail to conceive. To identify causal variants in patients with severe male infertility factor and repeated IVF failures, we sequenced the exome of two consanguineous family members who underwent several failed IVF cycles and were diagnosed with low sperm count and motility. We identified a rare homozygous nonsense mutation in a previously uncharacterized gene, RNF212B, as the causative variant. Recurrence was identified in another unrelated, infertile patient who also faced repeated failed IVF treatments. scRNA-seq demonstrated meiosis-specific expression of RNF212B. Sequence analysis located a protein domain known to be associated with aneuploidy, which can explain multiple IVF failures. Accordingly, FISH analysis revealed a high aneuploidy rate in the patients' sperm cells and their IVF embryos. Finally, inactivation of the Drosophila orthologs significantly reduced male fertility. Given that members of the evolutionary conserved RNF212 gene family are involved in meiotic recombination and crossover maturation, our findings indicate a critical role of RNF212B in meiosis, genome stability, and in human fertility. Since recombination is completely absent in Drosophila males, our findings may indicate an additional unrelated role for the RNF212-like paralogs in spermatogenesis.